Automated complex for thermoresistive properties investigation of nanostructured film systems - V.A. Zlenko; S.I. Protsenko; R. Safaric (Журнал нано- та електронної фізики)
Using industrial controllers of Advantech ADAM-4000 Company and system of graphic programming LabVIEW 8.6 the automated complex for thermoresistive properties investigation of film systems is developed. Approbation of the complex on example of Ni/Fe film system obtained by layered condensation is carried out.